From Iron Rice Bowl to Informalization : Markets, Workers, and the State in a Changing China - Gallagher, Mary Elizabeth, 1969-; Lee, Ching Kwan; Kuruvilla, Sarosh (Book collections on Project MUSE., 2011)
In this work a group of authors examines the nature, causes and consequences of informal employment in China at a time of major changes in Chinese society.